Wetland modelling - Mitsch, William J.; Straskraba, Milan; Jrgensen, Sven Erik, 1934- (Developments in environmental modelling, 1988)
The study of wetlands is a relatively new field and the modelling of these systems is still in its formative stages. Nevertheless, the editors felt compelled to assemble this volume as a first statement of the state of the art of modelling approaches for the quantitative study of wetlands. A global approach has been adopted in this book, not only by including a wide geographic distribution of wetlands, but also by including papers on both freshwater and saltwater wetlands. Wetlands are defined as systems intermediate between aquatic and terrestrial ecosystems, and include ecosystems.